Analisis Kemandirian Fiskal Pemerintah Daerah Kabupaten Pacitan dalam Mengurangi Ketergantungan terhadap Transfer Pemerintah Pusat - Naila Hanun Nazihah; Azkha Izatul Agista Putri; Indra Devian Lumban Gaol (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
This research aims to analyze the level of fiscal independence of Pacitan Regency by examining and linking it to its dependence on transfer funds from the central government. This study explores potential sectors that could be managed more optimally to contribute to Local Original Revenue (PAD). The method used in this research is a descriptive quantitative approach, utilizing secondary data, namely the Regional Budget (APBD) and Budget Realization Reports (LRA) sourced from the Directorate General of Fiscal Balance (DJKP). In addition to these sources, this research also employs a literature review of relevant journals. The analysis uses the regional financial independence ratio. The results of the analysis show that Pacitan Regency has a very high level of fiscal dependence, ranging between 85% and 89% from 2021 to 2025, although there is a gradual decline. The factors causing this condition are the low contribution of PAD, particularly from the tourism sector, as well as geographical factors such as mountainous terrain with underdeveloped infrastructure. This condition may lead to the flypaper effect and limit regional flexibility in development. This research recommends optimizing PAD from the tourism sector, improving regional financial governance, fostering collaboration with the private sector and the community, diversifying revenue sources, and gradually reducing dependence on transfer funds in accordance with the mandate of Law Number 33 of 2004.